Catalisadores heterogêneos para produção de chalconas: reação de condensação de Claisen-Schmidt - Winter, Caroline (2016)
The members of flavonoids and chalcones family have attracted great interest because of their pharmacological applications as antibacterial, anti-inflammatory and anticarcinogenicagents, and are commonly synthesized by Claisen-Schmidt condensation between acetophenone and benzaldehyde derivatives. This reaction is usually catalyzed under homogeneous conditions which present, however, several drawbacks such as catalyst recovery and waste disposal problems. This work proposes the use of a variety of heterogeneous catalysts to achieve good results for condensation Claisen-Schmidt reaction in terms of conversion and chalcones selectivity, when compared to the homogeneous catalysis. Two groups of catalysts were tested: metal oxides and activated carbons. Magnesium oxide catalysts were prepared by hydrothermal treatment and magnesium, niobium, lanthanum and titanium oxides by rehydration of commercial precursors, all methods followed and not followed by cesium impregnation. The activated carbons used as catalysts were Babassu, Bahia Coconut, ox bone and Dendê, raw and treated with sodium hydroxide. The catalysts were characterized by scanning and transmission electron microscopy, thermogravimetric analysis, differential thermal analysis, determination of the specific superficial area by the adsorption/desorption of N2 at 77 K method, infrared spectroscopy, X-ray diffraction and temperature-programmed desorption of CO2 and NH3. The basic sites of carbons were quantified by Boehm Method. Finally, the performance of the catalysts was evaluated on the Claisen-Schmidt reaction between Acetophenone and 4-nitrobenzaldehyde, and the conversion was quantified by high performance liquid chromatography. The best catalyst was treated babassu activated carbon, whose conversion achieved was 92,38%.